The Amicus Curiae of the Indonesian Advocates Association : Challenging the Rigidity of Criminal Procedure Law - Fauziah Lubis; Sayyid Al Umam Sitepu; Nur Syakirah (Jurnal Hukum, 2026)
This study aims to measure the impact of the Indonesian Bar Association's submission of an amicus curiae brief on public trust in criminal trial outcomes and to explain the social mechanisms behind this impact. Using normative juridical methods, this study finds that the Indonesian Bar Association's role as an amicus curiae has three significant social impacts on the criminal trial process in Indonesia. Media publicity is a necessary prerequisite. The social impact of the Indonesian Bar Association's amicus curiae brief is not inherent in the legal document itself, but arises from the interaction between professional legal intervention and public communication. For policy, this means that bar associations in civil law jurisdictions should integrate the drafting of legal documents. These findings provide evidence that non-state legal actors can restore institutional legitimacy through structured third-party intervention. For policy, this study offers a replicable model for advocate associations in civil law jurisdictions that seek to improve public accountability without sacrificing judicial independence. The role of the Indonesian advocate association in amicus curiae in the future can encourage Substantive Justice, thereby helping judges to understand the sense of justice that lives in society, so that decisions do not merely uphold the law procedurally.